Current Status of Wetlands in Srinagar City: Threats, Management Strategies, and Future Perspectives - Dar, Shahid Ahmad; Bhat, Sami Ullah; Rashid, Irfan; Dar, Sajad Ahmad (Frontiers in Environmental Science, 2020)
Wetlands are most diverse, highly dynamic, productive and ecologically sensitive areas of earth. In Kashmir Himalaya, Srinagar city is bestowed with a large number of picturesque wetlands. These wetlands are important in regulating ecosystem services such as providing fresh water supplies, food products, fisheries, water purification, harbour biodiversity and regulation of regional climate. These are also important as socio-economic support systems for the city inhabitants and valued as habitats of migratory birds that visit Kashmir valley from different continents of the world. Owing to the increased rate of anthropogenic activities and anthropogenically driven changes in natural processes, these wetlands are degrading at an alarming rate, seriously affecting their health and water quality. The major threats to wetlands include pollution, land use, and land cover changes, urbanization and encroachments and climate change. The intensive agricultural practices, introduction of exotic species and changes in hydrological flows during the past few decades have resulted in degradation of wetlands over this region. Sustainable Management of wetlands is crucial as these ecosystems offer an array of ecological functions that sustain livelihoods all over the world. This review provides special insights about the significant changes in spatial scale, land use and land cover changes and water quality of major wetlands in Srinagar city.